The Influence of The Professionalism Phases On Teacher's Performance - Wardoyo, Cipto (2015)
The study on teacher's rrclessionalism phaseehas been conducted by Hargreaves (2)00, which emended thalleaMer's orefessionalisrican be divined into 4 phases: 1) the pre professiona, 2) autonomous professional, 3) colegial professional and 4) post-professional Each of tnese phases desanbes the level of prolassiona ism that is closely related tc the teachers' performance. This finding isinterested lobe applec in Inds:nes-a due to the Act no 14 of 2005 on teachers arid lectuer who are considered asprofessional teacher. The purpose of this study is to describe and analyse the phases of professional teache• as %%Of as its Influence on the teachers performance (there are four hypotheses tc be tested).This slucey Was conducted a two vocational teachers in the field of Business and Management who consist of 159 teachers as popuatians.Theseiected sample technique is simple random Barron of 80 teachers i53% of 159). Data was col acted by using questionnaire, both for the dependent /unable and autonomous vahaoles; while the data analysis tothnlgue was dune by using multips 'near regressions that begin with the classical assumption The results showed tnat the pre-profess on phase. professional autonomous, and post- professional have significant postive effect on the teachers' performance: whereat the professional phase collegial has a significant effect or the teachers' performance. Tnis 1nding can be no the basis for rejecting the first and third hypothesis. On the otner way around. it accepts the second anc (outlet hypothesis.From the findings 0' the study, t is recommended that for similar research should develop a more in depth indicator of pro professional and pro'essona! variables to examine in depth collegial both from a literature review and the finding: of :inns research